Pancreatic stellate cells in pancreatic cancer: as potential targets for future therapy - Wang, Zhengfeng; He, Ru; Dong, Shi; Zhou, Wence (Frontiers in Oncology, 2023)
Pancreatic cancer is a strongly malignant gastrointestinal carcinoma characterized by late detection, high mortality rates, poor patient prognosis and lack of effective treatments. Consequently, there is an urgent need to identify novel therapeutic strategies for this disease. Pancreatic stellate cells, which constitute a significant component of the mesenchymal cellular layer within the pancreatic tumor microenvironment, play a pivotal role in modulating this environment through their interactions with pancreatic cancer cells. This paper reviews the mechanisms by which pancreatic stellate cells inhibit antitumor immune responses and promote cancer progression. We also discuss preclinical studies focusing on these cells, with the goal of providing some theoretical references for the development of new therapeutic approaches for pancreatic cancer.